Factors Affecting Gold Prices in Global Markets: Why is the Investment in Gold Safe? - Abedalfattah Zuhair Al-abedallat, (Journal of Humanities and Social Sciences Studies, 2026)
The study aimed to analyze Factors affecting gold prices in global markets, and why is the investment in gold safe? The research method applied in this study is a literature review, the qualitative approach that was designed to delve into the problem of the study through journals. Secondary sources for the study were books, articles and agency reports. In this essay, the literature of the supply and demand of gold, interest rate on US bonds, inflation and financial market uncertainty are critically reviewed. The study concluded that: Factors affecting the demand for gold and its price are: gold prices in foreign currencies set by central banks, particularly interest rates on the US dollar set by the Federal Reserve, the volume of demand for gold by central banks, due to the stability, and there are continued rise in global gold prices, despite the risks associated with investing in gold, such as price volatility, and  Gold and the US dollar are seen as having an inverse relationship. The study concluded an investor is supposed to diversify his investments by dividing them into three sections, for example: the first section is gold, the second section is cash in banks, and the third section is diversified investments (real assets and financial assets).